Intact provirus and integration sites analysis in acute HIV-1 infection and changes after one year of early antiviral therapy - Gabriella Rozera; Giuseppe Sberna; Giulia Berno; Cesare Ernesto Maria Gruber; Emanuela Giombini; Pietro Giorgio Spezia; Nicoletta Orchi; Vincenzo Puro; Annalisa Mondi; Enrico Girardi; Francesco Vaia; Andrea Antinori; et al. (Journal of Virus Eradication, 2022)
Background and objectives: HIV-1 provirus integration in host genomes provides a lifelong reservoir of virally infected cells. Although not able to generate viral progeny, the expression of defective proviruses has been associated with activation. Provirus integration may influence host gene transcription and shifts may occur during disease progression or antiretroviral therapy (ART). The study aimed to analyze intact/defective provirus and sites of provirus integration in acute infections: changes after 48 weeks of early therapy were also evaluated. Methods: DNA from peripheral blood lymphomonocytes of 8 acute HIV-1 infections at serodiagnosis (T0) and after 48 weeks of therapy (T1) was used to quantify intact and defective provirus by digital-droplet PCR and to analyze provirus integration sites, by next-generation sequencing of libraries derived from ligation-mediated PCR. Results: A high variability in the amount of intact proviral DNA was observed at both T0 and T1, in the different subjects. Although the ratio of intact/total proviral HIV-1 DNA did not dramatically change between T0 (8.05%) and T1 (9.34%), after early therapy both intact and total HIV-1 DNA declined significantly, p = 0.047 and p = 0.008, respectively. The median number of different (IQR) integration sites in human chromosomes/subject was 5 (2.25-13.00) at T0 and 4 (3.00-6.75) at T1. Of all the integration sites observed at T1, 64% were already present at T0. Provirus integration was observed in introns of transcriptionally active genes. Some sites of integration, among which the most represented was in the neuregulin 2 gene, were shared by different patients, together with the orientation of the insertion. Provirus integration was also observed in intergenic regions, with median (IQR) % of 15.13 (6.81-21.40) at T0 and 18.46 (8.98-22.18) at T1 of all read matches. Conclusions: In acute HIV-1 infection, the amount of intact proviral DNA in peripheral lymphomonocytes did not exceed 10% of total HIV-1 DNA, a percentage that was not substantially changed by early administrated ART. Provirus displayed a relatively small number of recurrent integration sites in introns of transcriptionally active genes, mainly related to cell-cycle control. Consideration should be given to therapeutic strategies able to target the cells harboring defective proviruses, that are not reached by conventional antiviral drugs, these potentially also impacting on replicative competent integrated provirus.